Providing Ergonomic Exercise Therapy To Reduce Joint Pain In The Elderly In Jember's Nursing Home - Kurdi, Fahruddin; Susanto, Tantut; Permatasari, Resi; Maharani, Feno Aureola (NHM PRESS, 2024)
Aging is a biological process where it is unavoidable, irreversible, and complex in nature which can have a negative impact on various organ systems and functions of human organs. One of them is the elderly experiencing a decrease in the musculoskeletal system. This can be marked by pain and stiffness in one or more joints. Therapy that can be done to reduce joint pain in the elderly includes physical sports activities or gymnastics which are the best alternative for dealing with joint pain in the elderly. Ergonomic exercise is one exercise that is recommended for the elderly. This study used a one group prepost test design. The population of this study was the elderly at UPT PSTW (Elderly Nursing Home) Jember. The sampling technique used was total sampling. The sample used in this study was 30 people. The intervention was carried out once a week. Pain scale measurements were carried out before and after the implementation of ergonomic exercises. Measurement of the pain scale using the Numeric Rating Scale (NRS) measuring instrument. Analysis of research data using the Paired Simple T-Test. The results of Group Activity Therapy used the Paired Simple T Test and obtained a significance value of 0.000 where the value of p <0.05 indicated that there was a significant difference in pain scale between pre-intervention and post- intervention.